Caracterización estructural de una vivienda tradicional indígena en el municipio de Ortega, Tolima – Resguardo Pijao Vuelta al Río (2019)
The westernization of Colombian indigenous peoples has lead to the decline of knowledge in how to build a traditional Indian house. In this graduation work study this ancestral knowledge was expressed through the structural characterization of a traditional home, in the Pijao Indian Reservation Community, Around the Corner of the River in the town of Ortega - Tolima. This was carried out in four stages: previous stage, as a bibliographic collection and the conception investigation method in a community in which was determined the participants ethnography; field stage, where the collection of the primary information took place in the reservation; developing stage, where the whole information process of the previous stage took place, realization of architectural and structural design, constructive process and it was compared with the Planning National Department TYPE 23 project (PND) and the Interior Ministry’s; in the final stage, the post process of the information that resulted in this writing was performed.